PEMANFAATAN KEGIATAN EKSTRAKURIKULER TARI TRADISIONAL “REOG PONOROGO” SEBAGAI UPAYA PELESTARIAN BUDAYA DI SEKOLAH DASAR - Alvia Dieska Aurilia; Eko Handoyo; Indriana Eko Armaidi (STKIP Subang, 2026)
Preserving local culture from an early age is essential to maintain cultural heritage amid rapid modernization. One effort that can be implemented is through Reog Ponorogo traditional dance extracurricular activities. This study aims to describe the utilization of Reog Ponorogo extracurricular activities as a cultural preservation effort in elementary schools. The research employed a literature review method by analyzing relevant national journal articles published within the last five years. The findings indicate that Reog Ponorogo extracurricular activities function as a medium for cultural introduction, cultural preservation, and character development. Through these activities, students learn about the history, cultural values, philosophy, and regional identity embedded in Reog Ponorogo. The activities also contribute to increasing students’ cultural awareness, creativity, and self-confidence. However, challenges remain, including the influence of modern culture, declining interest in traditional arts, and limited supporting facilities. Therefore, support from various stakeholders is needed to optimize the implementation of Reog Ponorogo extracurricular activities as a sustainable cultural preservation strategy.